Problems of restoration of window frames in the 19th century industrial facilities on the example of Łódź = Problematyka konserwatorska ślusarki okiennej w XIX wiecznych obiektach przemysłowych na przykładzie Łodzi - Walczak, Bartosz; Kurzac, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The introduction to the historical window frames in industrial facilities presents the historical background. The issue will be discussed on the example of 19th century industrial facilities, as well as in the context of the solutions applied in other European countries.
Keywords: ramy okienne; ślusarka okienna; obiekty historyczne; obiekty poprzemysłowe; problemy konserwatorskie; dziedzictwo postindustrialne; Łódź; window frames; post-industrial objects; postindustrial heritage; window maintenance